A macroprudential contagion stress test framework - Christian Bjørland; Thore Kockerols (Norges Bank, 2020)
We develop a macroprudential contagion stress test framework to examine how a network of Norwegian banks can amplify a shock to bank capital at the macro level. The framework looks at how fire sales of common asset holdings can lead to valuation losses for banks (indirect contagion), and how recapitalisation of banks can lead to direct contagion. We perform Monte Carlo simulations to quantify contagion-driven systemic risk and to evaluate the importance of the mechanisms in our model. Using data for 22 banks from 2019 Q2 we find that losses due to contagion can reach 2 percentage points (pp) of the banking sector's Common Equity Tier 1 (CET1) ratio, but most likely losses are around one-fourth of this. The losses result almost exclusively from indirect contagion. Further, we find that losses are high in the cases where banks quickly run into funding problems. We also find that market liquidity and which assets banks' fire sale first (pecking order) are important determinants of the results. Last but not least, losses due to contagion are highly correlated with losses on covered bonds.
hdl:11250/2659921
Keywords: C63; D85; G17; G21; 330; financial contagion; fire sales; bail-in; systemic risk